2014
DOI: 10.1530/joe-13-0306
|View full text |Cite
|
Sign up to set email alerts
|

IGF1R blockade with ganitumab results in systemic effects on the GH–IGF axis in mice

Abstract: Ganitumab is a fully human MAB to the human type 1 IGF receptor (IGF1R). Binding assays showed that ganitumab recognized murine IGF1R with sub-nanomolar affinity (KD=0.22 nM) and inhibited the interaction of murine IGF1R with IGF1 and IGF2. Ganitumab inhibited IGF1-induced activation of IGF1R in murine lungs and CT26 murine colon carcinoma cells and tumors. Addition of ganitumab to 5-fluorouracil resulted in enhanced inhibition of tumor growth in the CT26 model. Pharmacological intervention with ganitumab in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…Absence of Igf2 expression in the adult lung also reinforces the role of Igf1 as the major Igf1r ligand with auto/paracrine actions in this tissue, as demonstrated during fetal pulmonary development [29]. Actually, adult mouse lungs displayed the highest level of Igf1r activation of any organ in the mouse upon challenge with Igf1 [52]. This local auto/paracrine action of Igf1/Igf1rcould be relevant not only in airway epithelial cellregeneration, but also foralveolar macrophagefunction, a cell type that also expresshigh levels of both proteins[53, 54].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Absence of Igf2 expression in the adult lung also reinforces the role of Igf1 as the major Igf1r ligand with auto/paracrine actions in this tissue, as demonstrated during fetal pulmonary development [29]. Actually, adult mouse lungs displayed the highest level of Igf1r activation of any organ in the mouse upon challenge with Igf1 [52]. This local auto/paracrine action of Igf1/Igf1rcould be relevant not only in airway epithelial cellregeneration, but also foralveolar macrophagefunction, a cell type that also expresshigh levels of both proteins[53, 54].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, Igf1 and Igfbp3 systemic levels rise in mice with a pharmacological blockade of Igf1r, and also in patients with mutations of this gene [23, 52, 7779]. Since Igf1 and Igfbp3 levels have been involved in controlling colonic epithelial stem cell function [80], upregulation of their expression in the lungs of our Igf1r mutants could alter BASC function during airway epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that Igf1r deregulation decreases the number of peripheral white blood cells, thus providing evidence implicating Igf1r in promoting bone marrow myeloid cell generation. 28,29 The reduced eosinophil counts observed in blood and BALF from CreERT2 mutant mice led us to speculate that Igf1r could have an important role in proliferation and/or differentiation of myeloid progenitors and their recruitment to the lung, especially with respect to eosinophils. Further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…by tamoxifen (Janssen & Varewijck, ), rendering anti‐IGF1(R) therapeutics less effective. Furthermore, impaired signalling of IGF1R results in a compensatory feedback mechanism culminating in increased IGF1 production due to enhanced growth hormone secretion (Wan et al , ; Moody et al , ) (Fig. ).…”
Section: Therapeutics Resistance and Angiogenesismentioning
confidence: 99%